Guidelines for Developing Ethical Leadership of School Administrators Muang Tak School Group Affiliated to the Tak Primary Education Area Office, District 1 - Wongluang, Chaen; Yuttawong, Nontawat (Journal of Graduate MCU KhonKaen Campus, 2025)
This research aimed to: (1) examine the current state of ethical leadership among school administrators in the Mueang Tak school cluster under the Tak Primary Educational Service Area Offices 1 and 2; and (2) propose guidelines for developing ethical leadership among school administrators in the Mueang Tak school cluster under the Tak Primary Educational Service Area Office 1. A mixed-methods research design was employed. The population consisted of 95 school administrators and teachers in the Mueang Tak school cluster, selected through simple random sampling. The instruments used for data collection were questionnaires and interviews. Quantitative data were analyzed using the mean, standard deviation, and percentage, while qualitative data were analyzed through frequency distribution, ranking, and inductive analysis. The research findings were as follows: 1. Overall, the level of ethical leadership among school administrators in the Mueang Tak school cluster under the Tak Primary Educational Service Area Office 1 was at a high level. When considered by dimension, four dimensions were rated at a high level-justice, trust, respect, and responsibility-while integrity was rated at a moderate level. 2. The guidelines for developing ethical leadership among school administrators comprised: (1) Justice-administrators should adhere to ideals and ethical principles as guidelines for administration; (2) Trust-administrators should act as good role models to build confidence among subordinates; (3) Integrity-administrators should manage with transparency and uphold moral principles; (4) Respect-administrators should show respect and listen to colleagues’ opinions; and (5) Responsibility-administrators should possess knowledge and competence, be willing to take responsibility for decisions, and sincerely serve as a reliable support for subordinates.